2018
DOI: 10.1093/cid/ciy708
|View full text |Cite
|
Sign up to set email alerts
|

Tenofovir Diphosphate in Dried Blood Spots Is Strongly Associated With Viral Suppression in Individuals With Human Immunodeficiency Virus Infections

Abstract: TFV-DP in DBS is strongly associated with virologic suppression in PLWH on TDF-based therapy and is associated with certain participant characteristics. Further research is required to evaluate this drug adherence and exposure measure in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
125
5
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(149 citation statements)
references
References 39 publications
(56 reference statements)
14
125
5
1
Order By: Relevance
“…10 PrEP adherence measures vary widely between randomized controlled trials. [4][5][6][11][12][13][14][15] Although self-reported adherence measures seem to overestimate actual adherence, 16 trials measuring TFV-DP drug levels reported adequate adherence (corresponding to 4 or more tablets a week) in about 80%-90% of study participants, whereas near-perfect adherence (corresponding to 7 or more tablets a week) in 40%-50% of study participants. 17,18 However, these published data do not inform us about PrEP use and adherence after roll-off from PrEP trials and PrEP demonstration projects, when participants are challenged with establishing care, acquiring PrEP, and remaining adherent.…”
Section: Introductionmentioning
confidence: 99%
“…10 PrEP adherence measures vary widely between randomized controlled trials. [4][5][6][11][12][13][14][15] Although self-reported adherence measures seem to overestimate actual adherence, 16 trials measuring TFV-DP drug levels reported adequate adherence (corresponding to 4 or more tablets a week) in about 80%-90% of study participants, whereas near-perfect adherence (corresponding to 7 or more tablets a week) in 40%-50% of study participants. 17,18 However, these published data do not inform us about PrEP use and adherence after roll-off from PrEP trials and PrEP demonstration projects, when participants are challenged with establishing care, acquiring PrEP, and remaining adherent.…”
Section: Introductionmentioning
confidence: 99%
“…Persons with HIV receiving any tenofovir disoproxil fumarate (TDF)-based regimen (any duration of time), who attended a regular clinical visit where HIV viral load (VL) was routinely collected, were prospectively enrolled into a clinical cohort at the University of Colorado Hospital (UCH) Infectious Diseases Group Practice between 2014 and 2017, as previously described [ 1 ]. After informed consent was signed, whole blood (4–6 mL in ethylenediaminetetraacetic acid [EDTA]) was collected for DBS, and participants were observed for up to 3 routine visits over 48 weeks, allowing for a minimum of 14 days between visits [ 1 ].…”
Section: Methodsmentioning
confidence: 99%
“…Persons with HIV receiving any tenofovir disoproxil fumarate (TDF)-based regimen (any duration of time), who attended a regular clinical visit where HIV viral load (VL) was routinely collected, were prospectively enrolled into a clinical cohort at the University of Colorado Hospital (UCH) Infectious Diseases Group Practice between 2014 and 2017, as previously described [ 1 ]. After informed consent was signed, whole blood (4–6 mL in ethylenediaminetetraacetic acid [EDTA]) was collected for DBS, and participants were observed for up to 3 routine visits over 48 weeks, allowing for a minimum of 14 days between visits [ 1 ]. Three-month self-reported adherence was also evaluated at each visit using a validated visual analog scale that ranged from 0% to 100% [ 1 , 14 ], and HIV VL was measured through the Clinical Laboratory Improvement Amendments (CLIA)-certified clinical laboratory at UCH using quantitative polymerase chain reaction (Roche COBAS 6800; detection range of 20–10 000 000 copies/mL).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 On the other hand, TFV-DP has a longer half-life (17 days) and provides cumulative adherence information over a 30-day period. 24,27 TFV-DP drug levels are associated with health outcomes such as viral suppression in PLHIV, 28 efficacy of PrEP in HIV-negative people at risk of infection, 29 engagement in mental health care 20 among PLHIV, and the risk of viral rebound in PLHIV. 21 Immunoassays were recently developed to measure TFV in urine and blood.…”
Section: Introductionmentioning
confidence: 99%